Primary School Teachers’ Attitudes towards Inclusive Education for Learners with Visual Impairment in Jos South, Plateau State, Nigeria - Ugo, Elizabeth Aundu; Yakwal, Sylvester Mwandar (NIU Journal of Humanities, 2018)
The study examined primary school teachers’ attitudes towards inclusive education for learners with visual impairment in Jos South, Plateau state. One research question and one hypothesis were formulated to guide the study. The study adopted a survey research design with data obtained from respondents (n=150) using a researcher constructed Attitude towards Inclusive Education Scale (ATIES). One expert from the Department of Psychology and two experts each from the Departments of Educational Foundations and Special Education and Rehabilitation Sciences of the University of Jos respectively subjected the instrument to content validity. The test re-test method was utilized to determine the reliability of the instrument (reliability index= 0.75) using the Cronbach’s alpha reliability statistics. Data collected were examined for accuracy of entry and missing data after which they were analyzed using both descriptive and inferential statistics. Frequency count of opinions of teachers regarding inclusive education for learners with visual impairment was obtained using percentage, mean and standard deviation as well as z-scores to determine attitude direction. Based on results of the analysis, the study concluded that primary school teachers’ attitudes towards inclusive education for learners with visual impairment were negative. Recommendations were made to alleviate the situation as it was obtained in the area of study.